Diaphragm Function Parameters in Patients with Severe COVID-19 - A. Y. Yakovlev; A. A. Pevnev; M. S. Belous; V. N. Maksimychev; S. I. Chistyakov (Общая реаниматология)
The aim of the study was to investigate the feasibility of predicting the need for mechanical ventilation in patients with severe COVID-19 disease using ultrasound assessment of diaphragm function.Material and methods. An open prospective pilot study included 60 patients diagnosed with the novel coronavirus infection, who, at the time of admission to the intensive care unit (NEWS score > 6), underwent ultrasound assessment of diaphragm excursion, thickness and the diaphragm thickening fraction. Group 1 (n=30) included patients who did not require mechanical ventilation, and group 2 (n=30) consisted of patients who were subsequently transferred to mechanical ventilation.Results. Patients in group 2 had significantly lower diaphragm function parameters (left excursion value (P<0.001), right excursion value (P<0.001), diaphragm thickness on inspiration (P=0.043), and thickening fraction (P<0.001) than patients in group 1.Conclusion. Decreased diaphragm excursion of less than 17.1 mm on the right side is a predictor of initiation of mechanical ventilation in patients with the COVID-19 infection (sensitivity 93.3%, specificity 76.7%). Morphological examination in deceased patients of group 2 revealed pericellular and perivascular edema, venular thrombosis, endoneurial edema, and sludge in the lumen of arterioles.